SETNR/A: an agent-based secure payment protocol for mobile commerce. (12th July 2010) - Ou, Chung-Ming; Ou, C.R.
Non-repudiation of a mobile payment transaction ensures that when a buyer (B) sends some messages to a seller (S), neither B nor S can deny having participated in this transaction. An evidence of a transaction is generated by wireless PKI mechanism such that B and S cannot repudiate sending and receiving the purchase order respectively. SETNR/A protocol is proposed to improve the weakness of lacking non-repudiation mechanism from the secure electronic transaction (SET) protocol and SET/A for credit card-based transactions; on the other hand, agent-based protocol is ideal for complicated payment system. Broker generates a mobile agent for B which carries encrypted purchase order to S. A trusted third party (TTP) acts as a lightweight notary for evidence generations. One advantage of this agent-based payment protocol is to reduce inconvenience for mobile clients such as connection time and search for suitable merchant servers, etc.; it also provides necessary security mechanisms for mobile payment transactions.